Application and Strengthening Strategies of Network Resources in the Construction of Teaching Platform. Issue 4 (May 2021) - Liu, Hongyan
Abstract: Colleges and universities are at the forefront of popularizing and applying information technology, so it is necessary and responsible to create abundant teaching and learning resources, so as to provide a platform for teachers to carry out diversified teaching and students to carry out autonomous learning. In accelerating the process of educational informationzation, we should strengthen the development and application of high-quality educational resources, strengthen the construction of network teaching resources system, establish an open and flexible public service platform for educational resources, and promote the popularization and sharing of high-quality educational resources. In teaching, students should establish information concept, enhance information awareness, integrate, explore and apply computer professional knowledge with other courses, and effectively improve their information technology literacy and operational application ability. When using network resources, teachers need to search and download resources repeatedly with the help of search engines. In order to improve the availability of existing resources and integrate and share the scattered teaching resources, this paper proposes the development of the sharing information platform of network teaching resources in Colleges and universities.